2010
DOI: 10.1111/j.1471-0528.2010.02544.x
|View full text |Cite
|
Sign up to set email alerts
|

Randomised prospective single‐blinded study comparing ‘inside‐out’ versus ‘outside‐in’ transobturator tapes in the management of urodynamic stress incontinence: 1‐year outcomes from the E‐TOT study

Abstract: Objective To compare the 'inside-out' versus 'outside-in' routes for transobturator tape insertion for urodynamic stress incontinence, and to identify independent risk factors for failure at 1 year.Design Prospective single-blinded randomised trial.Setting Tertiary urogynaecology centre. Methods Women were randomised to tension-free vaginal tape-obturator (TVT)-OÔ for the 'inside-out' route (n = 170) and transobturator tape (TOT)-ARISÒ for the 'outside-in' route (n = 171). Participants completed validated symp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
51
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 76 publications
(56 citation statements)
references
References 36 publications
4
51
1
Order By: Relevance
“…The reported objective cure rates after MUS surgery are between 70 and 90%, changing according to definition of cure and follow-up time [17,18,19]. Our objective cure rates appear to be slightly higher than these values and also some of the previously reported randomized studies on Turkish women [20] in which objective cure rates at 12 months were 89 and 87% for RP and TO tapes, respectively.…”
Section: Discussioncontrasting
confidence: 40%
“…The reported objective cure rates after MUS surgery are between 70 and 90%, changing according to definition of cure and follow-up time [17,18,19]. Our objective cure rates appear to be slightly higher than these values and also some of the previously reported randomized studies on Turkish women [20] in which objective cure rates at 12 months were 89 and 87% for RP and TO tapes, respectively.…”
Section: Discussioncontrasting
confidence: 40%
“…Stav et al demonstrated a 86% success rate after TOT surgery in their series of 1225 patients (17). Some surgeon reported up to 91% cure rate after one year follow up (18). In this study, we achive 84 % cure rate after one year follow up period.…”
Section: Discussionsupporting
confidence: 60%
“…The authors concluded that both of these approaches were equally safe and clinically effective. Another randomized prospective study, [20] compared TVT and TOT patients, and did not determine a significant difference in terms of objective cure rate [21]. In our study, no significant difference in the objective cure rates of the patients in both groups (objective cure rate of the mesh group 85% and of the mesh free group 82% at the end of 24 month follow up).…”
Section: Discussionmentioning
confidence: 52%